Tax Knowledge, Tax Complexity and Tax Compliance in South Africa - Baneng Naape (Finance, Accounting and Business Analysis, 2023)
Purpose: the key objective of this study is to investigate the influence of tax knowledge and tax complexity on tax compliance in South Africa. Design: the data collection process involved self-structured questionnaires targeted at South African personal income taxpayers. The data was analyzed by means of descriptive analysis, inferential statistics and binary logistic regression. Findings: the findings from the Pearson correlation test revealed that knowledge on tax types, tax payment methods and tax penalties is positively associated with tax compliance and this association was found to be statistically significant. In addition, the results from the binary logistic regression revealed that knowledge on tax penalties is positively associated with higher probabilities of tax compliance and this association was likewise found to be statistically significant. This, to some extent, implies that tax penalties are well enforced by the government to induce tax compliant behaviour. Meanwhile, demographic factors such as the level of educational attainment as well as perceptions on the state of democracy were found to play a significant role in inducing tax compliance. Practical Implications: the study recommends the expansion of educational programmes that inform taxpayers about the different tax types they are liable for, the procedure for calculating and filing tax returns as well as the financial and legal consequences of exhibiting a tax non-compliant behaviour. Originality: The research topic is relevant for the management of tax systems especially during times wherein policymakers are in search of approaches to collect additional budget revenues. The study also presents a historical overview of problems that are observed in the income tax system of the Republic of South Africa, and this analysis is linked to the problems of tax compliance.
Keywords: H24; C51; 330; tax knowledge; tax complexity; tax compliance; South Africa